1996
DOI: 10.1897/1551-5028(1996)015<1844:pmaatr>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Macrophage Aggregates: A Toxic Response in Fish Exposed to Bleached-Kraft Mill Effluent?

Abstract: An epidemiological study was conducted to evaluate whether the density of pigmented macrophage aggregates (PMAs) and the prevalences of preneoplastic and neoplastic lesions increased in fish captured downstream from a bleached‐kraft pulp mill, causing induction of cytochrome P4501A enzymes (CYP1A). White suckers (Catostomus commersoni) sampled 10 and 95 km downstream from a bleached‐kraft pulp mill in the St. Maurice River, Quebec, Canada, exhibited higher densities of PMAs relative to age in liver, spleen, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…In mammalian non-estrogenic effects of nonylphenolic compounds include the production of ions and free radicals (ROS) (Obata and Kubota, 2000;Chitra and Mather, 2004;Okai et al, 2004;Gong and Han, 2006); moreover it has been shown that CYP-lA induction causes oxidant damage of cellular membranes (Couillard and Hodson, 1996). Therefore, the increase in melanin content reported herein may be interpreted as a reaction induced by oxidative stress and well correlated with CYP-1A induction.…”
Section: Discussionmentioning
confidence: 59%
“…In mammalian non-estrogenic effects of nonylphenolic compounds include the production of ions and free radicals (ROS) (Obata and Kubota, 2000;Chitra and Mather, 2004;Okai et al, 2004;Gong and Han, 2006); moreover it has been shown that CYP-lA induction causes oxidant damage of cellular membranes (Couillard and Hodson, 1996). Therefore, the increase in melanin content reported herein may be interpreted as a reaction induced by oxidative stress and well correlated with CYP-1A induction.…”
Section: Discussionmentioning
confidence: 59%
“…Elevated prevalence or size of macrophage aggregates have previously been used as an indicator of environmental degradation in a number of monitoring programs (Zdanowicz et al 1987;Bucke et al 1992;Long et al 1995;Fournie et al 2001). Exposure to heavy metals such as mercury (Meinelt et al 1997), pulp mill effluent (Couillard andHodson 1996), dioxins (van der Weiden et al 1994), crude oil (Khan and Kiceniuk 1984), polybrominated flame retardants (Raldúa et al 2008) and PCBs (Pierce et al 1980;Anderson et al 2003;Fisher et al 2008) leads to an increase in MAs. Bowser et al (1990) observed increased hepatic macrophage aggregates in brown bullhead collected at a site contaminated with PCBs and metals when compared to a reference site.…”
Section: Discussionmentioning
confidence: 99%
“…Couillard & Hodson (1996) reported a positive correlation between hepatic MA density and age in Catostomus commersoni (Lacépède) and proposed a link between MA formation and cytochrome P4501A peroxidase activity. Chromolipoids are abundant in the MAs of the liver, an organ that is particularly stressed in intensively reared fish, which shows typical cryptopathological, subclinical or asymptomatic transformation: cytoplasmic and nuclear vacuolizations which are characteristic of steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Wolke, 1992). Some authors have also proposed the use of MAs as biomarkers of environmental degradation and pollution (Wolke, 1992;Couillard & Hodson, 1996).…”
Section: Introductionmentioning
confidence: 99%